Early insights into the seasonal and spatial distribution of white sharks (Carcharodon carcharias) along the Maine coastline - Matthew M. Davis; Megan V. Winton; John A. Mohan; Joseph D. Iafrate; James A. Sulikowski; Blaise P. Jenner; Ashleigh J. Novak; Victoria Migneco; Tobey H. Curtis; Chip Michalove; Gregory B. Skomal (Frontiers in Marine Science, 2025)
While significant progress has been made to characterize life history patterns, movement ecology, and regional estimates of abundance of white sharks ( Carcharodon carcharias ) in the Western North Atlantic (WNA), patterns of spatial distribution remain relatively unknown in the northern Gulf of Maine. In this study, we utilize data collected from multiple acoustic telemetry projects from 2012-2023 to assess the spatiotemporal distribution of white sharks along sections of the Maine coastline and regional offshore waters. Acoustic receivers were deployed each year from 2012-2019 (mean number of receivers ± SD: 11 ± 4), and effort increased following the first-ever white shark related fatality in Maine in 2020 (2020-2023: 40 ± 15). In total, 107 white sharks tagged by researchers in the WNA were detected, with the majority (n = 90) detected in shallow (<50 m depth) waters post-2019. Reflective of the tagged population at-large, total length of individuals ranged from 2.1 to 4.9 m, with most individuals estimated to be in the juvenile or subadult life stages. White sharks were detected between the months of May-December, with peaks between July and September, and were observed in close proximity to several of Maine’s western beaches and islands/outcroppings, with higher numbers observed at several sites in eastern Casco Bay. Although the overall quantity of detections was relatively low when compared to white shark aggregation sites in other regions, this study provides baseline information on the presence of this species in the northern Gulf of Maine. While future research should include expanded receiver coverage in eastern Maine and the use of additional tagging technologies, this study contributes early insights for informing marine spatial planning, fisheries management, and conservation strategies for white sharks in the region.